2018
DOI: 10.1016/j.ctro.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilia as a biomarker for overall survival in newly diagnosed high-grade glioma patients undergoing chemoradiation

Abstract: HighlightsInflammation has been associated with poor outcome in various cancer histologies.In high-grade gliomas treated with concurrent temozolomide and radiation, pretreatment neutrophilia may be a significant prognosis factor for overall survival.In addition with previously available markers, this independent cost-effective biomarker could help identifying patients with worsened prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
3
28
0
1
Order By: Relevance
“…Conversely, others have shown that patients with neutrophilia prior to treatment have worse outcomes after radiation therapy in multiple cancer types (18). In patients with high-grade gliomas treated with concurrent temozolomide and radiation, pretreatment neutrophilia was a significant prognostic factor for poor overall survival (57).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, others have shown that patients with neutrophilia prior to treatment have worse outcomes after radiation therapy in multiple cancer types (18). In patients with high-grade gliomas treated with concurrent temozolomide and radiation, pretreatment neutrophilia was a significant prognostic factor for poor overall survival (57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Schernberg et al reported that pretreatment neutrophilia is negatively associated with overall survival in GBM patients who undergo concurrent treatment with TMZ and RT [43]. Baseline circulatory neutrophil count predicts bevacizumab efficacy in GBM patients, although the role of neutrophils in the antitumor response of anti-VEGF therapy is unclear [44].…”
Section: Circulating Neutrophils In Glioma Progression and Treatment mentioning
confidence: 99%
“…Neutrophils systemically and intratumorally accumulate in glioma patients and a high frequency of neutrophils is negatively associated with the prognosis of GBM patients [ 123 , 124 , 125 , 126 ] ( Figure 1 ). Moreover, the number of tumor infiltrating neutrophils correlates with glioma grade and represents a negative prognostic parameter for resistant patients [ 127 , 128 ].…”
Section: Neutrophils In Gbmmentioning
confidence: 99%